Sustainable prosthetic manufacturing: a comparative life cycle assessment of centralized and decentralized additive manufacturing supply chains in Europe - Feng, Jiarui; Daareyni, Amirmohammad; Flores Ituarte, Iñigo; Pagone, Emanuele (Springer, 2025)
Additive Manufacturing (AM) has emerged as a transformative ap-proach in prosthetic fabrication, offering personalized healthcare solutions along-side potential environmental advantages. This study investigates the environmen-tal sustainability of centralized and decentralized AM-based supply chains for prosthetic production across Europe. Utilizing a Life Cycle Assessment (LCA) framework and cradle-to-gate methodology, the analysis quantifies carbon foot-print (CFP) and water footprint (WFP) across raw material acquisition, manufac-turing, and transportation stages. Geospatial data from Google Maps and Great Circle Map were employed to model distribution routes within four European regions centered on Luxembourg. Centralized production was found to consistently outperform decentralized configurations in terms of environmental efficiency, largely due to reduced trans-portation-related emissions and resource use. In contrast, decentralized models, while offering increased responsiveness and customization, demonstrated ele-vated CFP and WFP values, particularly in regions with limited supplier accessi-bility or reliance on multimodal transport. By revealing the trade-offs between supply chain configurations, this study contributes to the development of sustainable manufacturing practices in healthcare. The findings underscore the importance of strategic supply chain de-sign, material selection, and integrated LCA in aligning AM processes with cir-cular economy principles and global sustainability goals.
The conference proceedings will be published by Springer as book chapters in a volume of the KES Smart Innovation Systems and Technologies series.
Keywords: Addictive manufacturing; Carbon footprint; Water footprint; Sustainability; Prosthetic; Prosthetics; Life cycle assessment; Supply chain; Cradle to gate